2020
DOI: 10.1002/pam.22202
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Effects of Early Algebra across California Middle Schools

Abstract: How should schools assign students to more rigorous math courses so as best to help their academic outcomes? We identify several hundred California middle schools that used 7th‐grade test scores to place students into 8th‐grade algebra courses and use a regression discontinuity design to estimate average impacts and heterogeneity across schools. Enrolling in 8th‐grade algebra boosts students’ enrollment in advanced math in ninth grade by 30 percentage points and eleventh grade by 16 percentage points. Math sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 50 publications
3
13
0
Order By: Relevance
“…Our study fills this gap and illustrates how contemporary methodological approaches can be used to evaluate treatment effect variation in settings where randomization is impossible. Thus, our study complements and informs recent discussions about the heterogeneity of ostensibly common policy shocks and contextual correlates that explain this heterogeneity (see, for example, McEachin, Domina, and Penner 2020;Orr et al 2019;Yeager et al 2019).…”
supporting
confidence: 79%
“…Our study fills this gap and illustrates how contemporary methodological approaches can be used to evaluate treatment effect variation in settings where randomization is impossible. Thus, our study complements and informs recent discussions about the heterogeneity of ostensibly common policy shocks and contextual correlates that explain this heterogeneity (see, for example, McEachin, Domina, and Penner 2020;Orr et al 2019;Yeager et al 2019).…”
supporting
confidence: 79%
“…Our results also underscore the complexities of policies that aim to accelerate students who are academically underprepared (e.g., Conger et al, 2020, 2021; Cortes et al, 2015; Hallett & Venegas, 2011; Jacob et al, 2017; Kolluri, 2018; McEachin et al, 2020; Troutman et al, 2018; Warne, 2017). Recent research from Texas found that college faculty concerned about the quality of high school DE courses wanted college credit to be tied to performance on a standardized final exam (Troutman et al, 2018).…”
mentioning
confidence: 56%
“…Many uses of test score data (whether from interim, benchmark, or summative assessments) focus on individual students' learning. For example, school leaders use test data to evaluate whether individual students are ready for grade advancement or graduation (e.g., Dougherty, 2015;Hamilton et al, 2009;McEachin, Domina, and Penner, 2020) or to inform students' course placement recommendations and to select students for specialized programming (e.g., Beaver and Weinbaum, 2015;Means, Padilla, and Gallagher, 2010). However, school-aggregate test score data are also an essential source of information.…”
Section: Study Background and Contextmentioning
confidence: 99%